Using vignettes to explore gender dimensions of household food security and nutrition - Elias, Marlène (Bioversity International, 2018)
Presented by Marlene Elias (GENNOVATE / Bioversity International), as part of the Annual Gender Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 27-28 September 2018.